1998
DOI: 10.5860/crl.59.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Using Transaction Log Analysis to Improve OPAC Retrieval Results

Abstract: This OPAC transaction log analysis study compared data derived from two sets of logs within a six-month period. Analysis of the first set of data revealed that users experienced difficulty with basic searching techniques. The OPAC introductory screens were simplified and clarified to help users improve search success rates. The second set of data, analyzed after screen changes had been made, showed statistically significant differ ences in search results. Regular monitoring of OPACs through transac tion log an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…Deborah Bleccic, et al conducted an analysis of transaction logs that indicated that users experience difficulty with basic searching techniques. 1 In a study conducted by Weijing Yuan, results indicate that searchers develop simple search strategies early on and tend to use these patterns repeatedly regardless of experience using the search engine.…”
Section: Resultsmentioning
confidence: 99%
“…Deborah Bleccic, et al conducted an analysis of transaction logs that indicated that users experience difficulty with basic searching techniques. 1 In a study conducted by Weijing Yuan, results indicate that searchers develop simple search strategies early on and tend to use these patterns repeatedly regardless of experience using the search engine.…”
Section: Resultsmentioning
confidence: 99%
“…There are various studies in which two sets of transaction log data were used to understand the usability and user-friendliness of search interfaces, one before any modifications in the interfaces and the other after the modifications. Earlier data for interfaces without modifications reveal that the users are not fully compatible with the basic search techniques, while the later show statistically significant differences in the results revealing that the modified interfaces are more compatible and userfriendly as the users show positive effect in their search attitude while working after the interfaces are being modified [23][24][25] . Designers are more likely to be successful in designing interfaces if they spend time with users, observing how they work…”
Section: Literature Reviewmentioning
confidence: 98%
“…Transaction logs have been used successfully to improve user interfaces of traditional OPACs in libraries. 4 This article discusses the use of transaction logs to improve the user interface for the ASDB. The logs analyzed herein represent usage from October 2000 through September 2001 for the initial user interface and usage from February 2002 through April 2002 for the improved user interface.…”
Section: Approach and Methodologymentioning
confidence: 99%